2021
DOI: 10.1101/2021.05.23.445322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alpha Oscillatory Activity Causally Linked to Working Memory Retention: Insights from Online Phase-corrected Closed-loop Transcranial Alternating Current Stimulation (tACS)

Abstract: Although previous studies have reported correlations between alpha oscillations and the "retention" sub-process of working memory (WM), no direct causal evidence has been established in human neuroscience. Here, we developed an online phase-locking closed-loop transcranial alternating current stimulation (tACS) system capable of precisely controlling the phase difference between tACS and concurrent endogenous oscillations. This system permits both up- and down-regulation of brain oscillations at the target sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
(137 reference statements)
0
2
0
Order By: Relevance
“…In a study done by Riddle et al, 26 authors found parietal alpha had a causal role for information suppression in WM. In the pre-print version, Chen et al, 27 indicate a causal link between alpha power and retention in WM. In the mentioned study, researchers apply transcranial alternating current stimulation (tACS) in both in-phase and anti-phase stages to link these interventions with EEG data but also with behavioral outputs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study done by Riddle et al, 26 authors found parietal alpha had a causal role for information suppression in WM. In the pre-print version, Chen et al, 27 indicate a causal link between alpha power and retention in WM. In the mentioned study, researchers apply transcranial alternating current stimulation (tACS) in both in-phase and anti-phase stages to link these interventions with EEG data but also with behavioral outputs.…”
Section: Introductionmentioning
confidence: 99%
“…In the mentioned study, researchers apply transcranial alternating current stimulation (tACS) in both in-phase and anti-phase stages to link these interventions with EEG data but also with behavioral outputs. 27 Inhibition of unrelated information suppression is a crucial aspect of not only WM but also video game pro ciency, an experience that highly relies on VWM function. Inhibition of non-task-related stimulus processing may be necessary to perform a visual scanning task with high e ciency.…”
Section: Introductionmentioning
confidence: 99%